IMMERSIVE LEARNING BASED FLOOD SIMULATION USING 3D ARCSCENE 10.8 FOR DISASTER MITIGATION EDUCATION - Harjanti, Diah Trismi; Somantri, Lili; Apriliyana, Muhammad Iqbal; Arini, Audi Cindra; Javada, Aliiffillya; Setiawan, Iwan (Jurnal Visi Ilmu Pendidikan, 2026)
In the era of technological advancement, geography education is evolving through digital transformation. This study aims to develop simulation media using 3D ArcScene to support immersive learning in the context of disaster mitigation, particularly flood disasters. By providing realistic 3D representations, the media helps students better understand flood scenarios and appropriate mitigation strategies. The development follows a Research and Development (R&D) approach with quantitative methods, focusing on improving student competencies in geography-related subjects such as land use, meteorology, climatology, and environmental ecology. The study specifically models flood-prone areas in Sanggau Regency, producing interactive visualizations that can be integrated into disaster geography courses. The goal is to enhance student engagement and comprehension through immersive and technology-based learning experiences. Ultimately, this simulation media is expected to serve as an effective tool for building student awareness and resilience, as well as contributing to the advancement of immersive educational resources in disaster mitigation efforts.